ผลของชนิดซีโอไลต์ต่อการสังเคราะห์ไดเมทิลอีเทอร์ที่อุณหภูมิต่ำ - สิริรัตน์ อยู่เวียงไชย (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The direct synthesis of dimethyl ether (DME) from syngas has been investigated on the composite catalysts, CuZnO/zeolites (HZSM-5,Y, modenite). The study was carried out in a continuous semi-batch reactor at pressure of 40 bar and the ratio H₂/CO of 1:1. The composite catalysts were synthesized using the combination method between co-precipitation of Cu-Zn and mechanicall mixing with zeolites. The effects of various zeolites have been studied to determine an optimum condition and development of highly active catalyst to the direct synthesis of dimethyl ether (DME) from syngas at low temperature. The catalysts were characterized by X-ray diffraction (XRD), Nitrogen isotherm (BET), Temperature-programmed reduction (TPR) and NH3 Temperature programmed desorption (NH3-TPD). The experimental results indicated that CZ/HZSM-5 catalyst provided the highest CO conversion of 28.82% with DME selectivity of 69.6% at the temperature of 170℃ and the ratio CZ/HZSM-5 of 2:1.